2017
DOI: 10.1021/acsnano.7b05234
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity of Double-Stranded RNA-Antimicrobial Peptide Complexes Modulates Toll-Like Receptor 3-Mediated Inflammation

Abstract: Double-stranded RNA (dsRNA) induces production of pro-inflammatory cytokines in normal human epidermal keratinocytes (NHEK) by specific binding to endosomal Toll-like receptor-3 (TLR3). Recently, it has been shown that hyperactivation of TLR3 in psoriatic keratinocytes by dsRNA can occur in the presence of human antimicrobial peptide (AMP) LL37. Here, we combine synchrotron X-ray scattering, microscopy, computer simulations, and measurements of NHEK cytokine production to elucidate a previously unanticipated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 60 publications
5
46
0
Order By: Relevance
“…This structure is consistent with close contact and charge compensation between the cationic peptides and anionic dsRNA, with a spatial periodicity of 3.76 nm and 3.70 nm between adjacent dsRNA within the complex (respective nanocrystal sizes of L = 9.0 nm and 16.6 nm). Interestingly, the structure of the LL34(I20P)-dsRNA complex is consistent with the capacity to enable dsRNA to be recognized by TLR3 31 . Therefore, we concluded that it was unlikely that the loss of immunological activity of LL34(I20P) was due to disruption of binding and structured complex formation with dsRNA or interference with TLR3 recognition.…”
Section: Resultssupporting
confidence: 52%
“…This structure is consistent with close contact and charge compensation between the cationic peptides and anionic dsRNA, with a spatial periodicity of 3.76 nm and 3.70 nm between adjacent dsRNA within the complex (respective nanocrystal sizes of L = 9.0 nm and 16.6 nm). Interestingly, the structure of the LL34(I20P)-dsRNA complex is consistent with the capacity to enable dsRNA to be recognized by TLR3 31 . Therefore, we concluded that it was unlikely that the loss of immunological activity of LL34(I20P) was due to disruption of binding and structured complex formation with dsRNA or interference with TLR3 recognition.…”
Section: Resultssupporting
confidence: 52%
“…Cognate to LL37-DNA complexes, we found that LL37-dsRNA complexes formed nanocrystalline structures with well-defined inter-dsRNA spacings, and that complexes that maximally activated TLR3 had spacings perfectly matched with the steric size of TLR3. A mathematical model and computer simulation of TLR3 binding to spatially periodic AMP-dsRNA complexes recapitulated the experimental data and showed that both the inter-dsRNA spacing and the number of repeat units within the complexes were primary determinants of immune activation (56). This validated the idea that innate immune receptors like TLR9 and TLR3 can recognize both single ligands, as well as the crystallinity of spatially periodic, geometrically patterned ligands templated by molecular chaperones like AMPs.…”
Section: Amps Organize Immune Ligands Into Spatially Periodic Nanocomsupporting
confidence: 54%
“…We found that the complex formed by LL-37 and dsRNA binds to scavenger receptors and causes uptake of the complex into the intracellular space [98]. We also demonstrated that LL-37 and similar α-helical AMPs can form pro-inflammatory nanocrystalline complexes with dsRNA that are recognized by TLR3 differently from dsRNA alone [101]. Self-nucleic acids (DNA, RNA) are DAMPs released from damaged cells and extracellular matrix to activate the innate immune system.…”
Section: Scavenger Receptors and Ampsmentioning
confidence: 83%